PENGARUH PENATAAN TEMPAT DUDUK DAN METODE PEMBELAJARAN PROBLEM BASED LEARNING (PBL) TERHADAP MOTIVASI BELAJAR - Muhammad Fadzillah Fuadi aldi; Ali Ismail; Aah Ahmad Syahid (Universitas Muhammadiyah Kuningan, 2024)
Horseshoe seating formation is a student seating arrangement method designed to create optimal interaction and communication in the classroom and for the Problem Based Learning (PBL) method learning strategy as a means to achieve effective learning objectives. This study aims to determine the effect of horseshoe seating arrangement and the Problem Based Learning (PBL) method on the science learning motivation of fifth grade students at SDN Bunter 1. The type of research is quantitative with experimental research methods. The design used pretest-posttest control group design. The samples of this study were VA class students as control class and VB as experimental class with a total of 72 students. The research sample was determined using purposive sampling. Data analysis using SPSS software version 20.0 for windows. The results showed that the significance value for the seating arrangement was 0.00 <0.05 while the significance value for the Problem Based Learning (PBL) learning method was 0.00 <0.05, this means that H0 is rejected Ha is accepted. The research conclusion shows that there is a positive influence of seating arrangement and Problem Based Learning (PBL) learning method on student learning motivation.